Experimental investigation and parametric studies on structured packing chamber based liquid desiccant dehumidification and regeneration systems. (February 2019) - Naik, B. Kiran; Muthukumar, P.
Abstract: In this paper, an experimental investigation carried out for estimating the overall energy exchange between the liquid desiccant and the ambient air is presented. The influence of air humidity ratio on the performance of the liquid desiccant dehumidification/regeneration system is studied in detail. A correlation for humidity ratio difference between the process air inlet and exit of the packed chamber in terms of known operating parameters is developed for both dehumidification and regeneration systems. A two–dimensional thermal model is proposed for predicting the performance of the adiabatic counter – flow liquid desiccant dehumidifier/regenerator. The proposed model is validated with the experimental data and found accurate. Influences of air humidity ratio, L/G ratio and Lewis number on the latent heat ratio of both the dehumidification and the regeneration systems are analysed. Using Derringer's desirability function method, for a given range of operating parameters, optimal inlet condition for the maximum humidity ratio difference between the inlet and the exit of the dehumidification/regeneration system is obtained. Graphical abstract: Image 1 Highlights: Performance of dehumidification and regeneration systems are tested experimentally. Developed correlations for humidity ratio difference along the packed chamber. Analysed transfer process at the interface of water and air using a thermal model. Investigated the effect of Lewis number (Le) on evaporation and condensation rates. Predicted optimum conditions to obtain a maximum specific humidity difference.